Comparison of kinesio taping and sports taping in functional activities for collegiate basketball players: A pilot studie - Tsai, C. -H.; Chang, H. -Y.; Chen, T. -Y.; Chen, H. -C. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
The purpose of this study was to identify the effects of kinesio taping and sports taping for collegiate basketball players in functional activities. Seventeen collegiate basketball players were recruited in particapitate this study and divided into three groups(Kinesio taping group, sports taping group and control group) in random. The ankle range of motion, plantarflexor muscle strength and endurance, vertical jump, and dynamic balance were measured before and after taping applied. The results was showed significantly increasing in ankle plantar-flexion range for Kinesio taping group (p=.03). There were no remarkable difference in the other measurements. In conclusion, the Kinesio Taping would not restriction the ankle plantar-flexion range. In future, we may recruited more subjects to identify the effect of Kinesio taping in functional activities for collegiate bsketball players.